Carbonation rate of compacted recycled aggregates for sub-base layers of pavement. (20th December 2021) - Hou, Yunlu; Mahieux, Pierre-Yves; Lux, Jérôme; Turcry, Philippe; Aït-Mokhtar, Abdelkarim
Highlights: The carbonation rate of compacted recycled aggregates (RA) is about ten mm per year 1/2 . CO2 fixation potential of compacted recycled aggregates is significant, it can reach about 30 kg/m 3 . It is preferable to carbonate RA prior to their placing given the slowness of their carbonation on site once they are compacted. Compacted recycled aggregates could provide a carbon sink. Abstract: Recycled aggregates are mainly composed of demolition concrete aggregates, i.e., reactive materials that can bind CO2. The aim of the present study was to investigate the carbonation of recycled aggregates after compaction for road layers construction. Experiments were carried out on samples of compacted recycled sand kept in various moisture conditions. Carbonation was investigated by means of pH indicator spraying, thermogravimetric analysis and CO2 diffusion tests. The results show that the carbonation rate of compacted recycled aggregates is of the order of about ten millimetres per year 1/2 . Recycled aggregates after compaction constitute a significant carbon sink since a maximum of 30 kg of CO2 is bound per m 3 . However, from an application point of view, it seems preferable to carbonate the recycled aggregates before they are placed in their final environment to achieve all benefits of carbonation.